Chemical vs. natural toothpaste: which formulas for which properties? A scoping review - Aida Kanouté; Serigne Ndame Dieng; Mbathio Diop; Amadou Dieng; Ayotollah Khoumeyni Sene; Massamba Diouf; Cheikh Mbacké Lo; Daouda Faye; Florence Carrouel (AOSIS, 2022)
Introduction.  The proliferation of the oral care industry has made it more challenging for shoppers to zero in on the best possible toothpaste for their preventative requirements. It also makes the toothpaste's various components safer. Objective.  The researchers set out to evaluate the state of information about the biological properties and cytotoxicity of adult toothpaste so that they might make some informed recommendations. Methods.  A scoping review of research published between 2015 and 2020 according to PRISMA guidelines was performed. Results.  In vitro clinical trials account for 44% of the papers, in vivo clinical trials for 25%, systematic reviews for 19%, and meta-analyses for 12%. They have active chemical components that have been shown to be antimicrobial, anti-inflammatory, or desensitizing. Herbal toothpaste has these characteristics and is very secure to use. Toothpaste with sodium lauryl sulfate has been found to be harmful. Conclusions.  Scientists have investigated the biological effects of a wide range of chemically active compounds and plant extracts. Herbal toothpaste, it has been discovered, is both efficient and secure. Companies making toothpaste should be required to clearly label the product's qualities, active ingredients, and potentially harmful ingredients on the packaging.